2017
DOI: 10.1177/0305735617712424
|View full text |Cite
|
Sign up to set email alerts
|

Music for anxiety? Meta-analysis of anxiety reduction in non-clinical samples

Abstract: The beneficial influence of listening to music on anxiety states has often been discussed. However, the empirical evidence and theoretical mechanisms underlying these effects remain controversial. The aim of this study is to conduct a meta-analysis of randomized controlled trials on the effects of music on anxiety in healthy individuals. A comprehensive search in the PsycINFO, Cochrane Library, PubMed and Web of Knowledge databases produced 19 articles complying with the eligibility criteria. The main results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(74 citation statements)
references
References 58 publications
5
66
1
2
Order By: Relevance
“… Koelsch (2014) indicated that music elicited changes in the cerebral regions underlying emotion (limbic and paralimbic areas) in adults, similarly to full-term newborns ( Perani et al, 2010 ). Moreover, music listening had also positive effects on stress and anxiety reduction, suggesting that it improved emotion regulation abilities ( Van Goethem and Sloboda, 2011 ; Linnemann et al, 2015a ; Panteleeva et al, 2018 ). Our preliminary findings are consistent with the literature supporting that music listening has positive effects in emotion processing and regulation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“… Koelsch (2014) indicated that music elicited changes in the cerebral regions underlying emotion (limbic and paralimbic areas) in adults, similarly to full-term newborns ( Perani et al, 2010 ). Moreover, music listening had also positive effects on stress and anxiety reduction, suggesting that it improved emotion regulation abilities ( Van Goethem and Sloboda, 2011 ; Linnemann et al, 2015a ; Panteleeva et al, 2018 ). Our preliminary findings are consistent with the literature supporting that music listening has positive effects in emotion processing and regulation.…”
Section: Discussionmentioning
confidence: 97%
“…Listening to music is a complex cerebral process, as it involves auditory, cognitive, motor, and emotional functions soliciting widespread activation of various neuronal networks ( Koelsch, 2014 ; Sihvonen et al, 2017 ). Studies showed that listening to music had positive effects on stress and anxiety reduction in healthy adults ( Linnemann et al, 2015a ; Panteleeva et al, 2018 ) and newborns ( Rossi et al, 2018 ), as well as for pain-reduction in patients with chronic pain disease ( Linnemann et al, 2015b ) or in postoperative patients who had various types of major surgery ( Hole et al, 2015 ). These studies suggest that music intervention may enhance self-regulatory abilities.…”
Section: Introductionmentioning
confidence: 99%
“…A promising research area is therefore the investigation of whether the development of mindfulness skills would predict a decrease in psychopathological symptoms and improved the academic performance in university students. Future studies could also explore whether mindfulness-based interventions adapted to students’ needs and other techniques, such as listening to music (Panteleeva, Ceschi, Glowinski, Courvoisier, & Grandjean, 2018), may be useful for improving well-being and academic success in a university population.…”
Section: Discussionmentioning
confidence: 99%
“…Panteleeva et al, 2017). Music listening involves auditory, cognitive, motor, and emotional functions across cortical and subcortical brain regions (Koelsch, 2014).…”
Section: Introductionmentioning
confidence: 99%